2015
DOI: 10.3141/2512-07
|View full text |Cite
|
Sign up to set email alerts
|

User Satisfaction and Its Impacts on the Use of a Public Bicycle System

Abstract: This research examined the evaluation of service quality in the public bicycle system (PBS) in Hangzhou, China, along with a measurement of user satisfaction, and of how an individual's perceived satisfaction influenced his or her PBS use. A 30-item PBS service quality scale was first developed and then applied to the empirical study of PBS service in Hangzhou. On the basis of a finally validated sample of 231 responses, an item-based PBS service quality assessment and an individual-based satisfaction assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Zhang et al [24] mentioned that vehicle tracking technology may play an important role in solving the problem of uncivilized behaviors. However, they neither explained why nor tested whether this is true.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [24] mentioned that vehicle tracking technology may play an important role in solving the problem of uncivilized behaviors. However, they neither explained why nor tested whether this is true.…”
Section: Resultsmentioning
confidence: 99%
“…Efthymiou et al [23] focus on personal characteristics and find that income, age and environment conscious influence people's intention to use. Zhang et al [24] summarized 30 items to measure user satisfaction towards bike-sharing scheme and found that perceived satisfaction is an important antecedent of public bike-sharing usage.…”
Section: Challenges Of Bike-sharing Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Research concerning user satisfaction for BSSs includes analyses carried out in Canada (Bachand-Marleau et al, 2012;El-Assi et al, 2015), the United States , Australia (Fishman et al, 2014) and the United Kingdom (Kingham et al, 2001). The China case is analysed by and, for the case of the world's biggest BSS in Hangzhou, by Zhang et al (2015a). One shared feature of these studies is that they are presented as a result of a research project proposed to and conducted in partnership with the institutions owning and managing the BSSs, being seldom conducted independently (see also Kingham et al, 2001;Grigoroudis & Siskos, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The impacts of built environment factors on the trip demand and the ratio of demand to supply at bike stations were investigated in the paper [23]. The service quality of the PBS in Hangzhou was evaluated and user satisfaction was measured; positive feedback was received from the respondents [24]. Visual analysis techniques offer an opportunity to extract meaningful information from PBS data.…”
Section: Data Descriptionmentioning
confidence: 99%